The geography of capital allocation in the euro area - Roland Beck; Antonio Coppola; Angus Lewis; Matteo Maggiori; Martin Schmitz; Jesse Schreger (European Central Bank (ECB), 2024)
We assess Euro Area financial integration correcting for the role of "onshore offshore financial centers" (OOFCs) within the Euro Area. The OOFCs of Luxembourg, Ireland, and the Netherlands serve dual roles as both hubs of investment fund intermediation and centers of securities issuance by foreign firms. We provide new estimates of Euro Area countries' bilateral portfolio investments which look through both roles, attributing the wealth held via investment funds to the underlying holders and linking securities issuance to the ultimate parent firms. Our new estimates show that the Euro Area is less financially integrated than it appears, both within the currency union and vis-à-vis the rest of the world. While official data suggests a sharp decline in portfolio home bias for Euro Area countries relative to other developed economies following the introduction of the euro, we demonstrate that this pattern only remains true for bond portfolios, while it is artificially generated by OOFC activities for equity portfolios. Further, using new administrative evidence on the identity of non-Euro Area investors in OOFC funds, we document that the bulk of the positions constituting missing wealth in international financial accounts are now accounted for by United Kingdom counterparts.
Keywords: F3; F4; G2; G3; H26; 330; Financial Integration; Capital Markets Union; Home Bias